Hadith #3390 - Sunan Abi Dawud - Ibrahim bin Sa'd bin Ibrahim إبراهيم بن سعد بن إبراهيم; Muhammad bin 'Abdur Rahman bin Labayba محمد بن عبد الرحمن بن لبيبة; Sa'd ibn Abi Waqqas; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Uthman bin Muhammad; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
That Zayd ibn Thabit said: May Allah forgive Rafi’ ibn Khadij. I swear by Allah, I have more knowledge of Hadith than him. Two persons of the Ansar (according to the version of Musaddad) came to him who were disputing with each other. The Messenger of Allah (ﷺ) said: If this is your position, then do not lease the agricultural land. The version of Musaddad has: So he (Rafi’ ibn Khadij) heard his statement: Do not lease agricultural lands.
Grade: Hasan